The Role of Religion and its Influence on Conflicts in Nigeria - Bursać, Boris (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
At the very end of colonial rule, UK established Islam and Christianity in Nigeria as the two dominant religions with the middle belt region of Nigeria as the battle ground. Before their final departure, they secured and formed several ethnic and religious lines, which in the postcolonial era were used by political elites as a way to fight for state power. As such, on the basis of the abuse of political and religious elites, and on the basis of ethnic, religious and regional divisions, a deeply fragmented Nigeria as we know it today emerged. With colonial domination, sudden transitions, the power of society was destroyed to such an extent that it became incapable of regulating human passion. The situation is further heated by leading elites who manipulate religious identity, where as a result appears that the north of Nigeria, mostly Muslim, tends to Islamize the whole Nigeria, and the south, mostly Christian, strives to defend Christianity and the constitutional secularism of the state. In such a situation, religion, instead of calming passions and tensions, thanks to its leaders, opens the way to conflict, violence, extremism, and, finally, terrorism. The central understanding of the formation of the identity of religion and its transformation from conflict to violence is the rise of religious extremism throughout the country. Extremist groups show significant intolerance towards members of their own and other religions, react to social, economic and political crises of Nigerian politics, of course in religious terms, which later leads to conflicts. The integration of religion into Nigerian politics, which we can thank the colonial rulers, is one of the leading problems and it is precisely this that stands behind religious violence and political instability in the country.